Turuk Bintul Gastronomy in the Dimension of Islamic Education - Moh Sakir; Robingun Suyud El Sham (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study is focused on answering the social problems of turuk bintul gastronomy in the dimension of Islamic education. A qualitative approach in the setting of library research is used to answer these problems. The results showed that etymologically the name turuk bintul looks dirty, meaning female genitals with lumps. However, the purpose of this name is not to emphasize this aspect, but rather to focus on delicious and savory foods. The dimension of Islamic education is the importance of thinking clearly in responding to everything around us. In Islam, the term clear-minded is synonymous with husnuzon, which means to think clearly and think well about things or other parties. By responding in this way, the effect of this action will be good as well. This research hopes to contribute to Islamic education related to positive thinking.